Photosynthesis and foliar vascular adjustments to growth light intensity in summer annual species with symplastic and apoplastic phloem loading - Polutchko, Stephanie K (Journal of plant physiology, 2021)
Copyright © 2021 Elsevier GmbH. All rights reserved.